Visualization of Thermal Effects in Polypropylene-based Composites under Cyclic Bending Tests. (2016) - Boccardi, Simone; Carlomagno, Giovanni Maria; Meola, Carosena; Simeoli, Giorgio; Russo, Pietro
Abstract: The attention of this paper is focused on surface temperature changes which are experienced by thermoplastic composite materials under cyclic bending tests. Such changes are visualized and measured with an infrared imaging device and later analyzed to gain information which, coupled with other mechanical and/or chemical properties, may be exploited for the material characterization. In particular, thermoplastic composites based on a polypropylene matrix, which may be neat, or modified by the addition of a relatively low amount of a specific compatibilizing agent, and reinforced with glass or jute woven fibres are investigated.